Avaliação da ampliação foraminal, centralização do preparo apical, características geométricas e flexibilidade de instrumentos reciprocantes Reciproc Blue R25 e duas réplicas - Cícero Ferreira Maia (2023)
One of the biggest challenges in Endodontics is to overcome the great morphological variability of the root canal system and promote an adequate disinfection in all its extension. Transport of the apical foramen can lead to complications in subsequent cleaning and obturation procedures. This work aimed to evaluate, by means of Scanning Electron Microscopy (SEM), the morphological alterations, and the enlargement and centralization of the apical preparation after instrumentation of root canals in extracted teeth using Reciproc Blue R25 reciprocating files, and two of its replicas, systems NiTi TDK V-File and UnivyOne. Forty-eight extracted premolars were used and divided into 9 groups. Each group with 7 canals was instrumented with one of the 3 file systems evaluated and in one of the 3 following situations: working lengths in the foramen (RB0, VF0 and UO0), one millimeter beyond the foramen (RB1, VF1 and UO1) and two millimeters beyond the foramen (RB2, VF2 and UO2). The study also related the behavior of these instruments to their flexibility and geometric characteristics. To evaluate the morphological alterations of the apical foramen after foraminal enlargement, the root apexes of the teeth were analyzed using Scanning Electron Microscopy, SEM. The enlargement of the foramen and the occurrence of apical transport was measured from images before and after canal preparation according to area measurements and Feret analysis of the apical foramen using ImageJ software. The images were evaluated by 1 previously trained and calibrated examiner. High resolution photos and the Image J 1.48V software were used to measure the total length and diameters at each millimeter of the active part of the instruments (n=10). The flexibility of the instruments (n=10) was checked through bending tests at 45° using a testing machine (Analógica, Belo Horizonte, MG, Brazil) built based on the ISO 3630-1 specification (International Organization for Standardization, 1992). All observed values were noted down and the statistical analysis was performed using the SPSS – Statistical Package for the Social Sciences program. Descriptive analyzes were performed using absolute, mean, median, standard deviation and amplitude frequencies. The Shapiro-Wilk normality test was used to evaluate the distribution of continuous variables according to the groups and file systems analyzed. For variables with normal distribution, one-way ANOVA with Tukey's post-test and paired t test were performed. For variables with non-normal distribution, Kruskal-Wallis tests were performed with Dunn post-test and Wilcoxon test. For all tests, a significance level of 5% was considered. The results showed that, regarding foraminal enlargement, all canals showed an increase in the final area compared to the initial area, with no statistical difference between the instrument systems and working lengths evaluated. No difference was found in the Feret Ratio obtained for the groups, both before and after instrumentation, demonstrating that there was no significant apical transport in any of the evaluated situations. Reciproc Blue file system had a smaller diameter in the D1 diameter measurements, when compared to the V-File file system (P = 0.021), and in the D3 and D4 measurements, when compared to the Univy One file system (P = 0.039 and P = 0.017, respectively). In the flexibility tests, the Univy One system was more flexible and the V-File less flexible (P<0.001). The study concluded that although the Reciproc Blue systems and their replicas are not the same in terms of geometry and flexibility, there was no difference between them in terms of foraminal enlargement and apical transport, in any of the evaluated situations.